2017
DOI: 10.1038/s41598-017-05281-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality Measurement of Two-dimensional Shear Wave Speed Imaging for Breast Lesions: the Associated Factors and the Impact to Diagnostic Performance

Abstract: This study aimed to identify the associated factors for quality measurement (QM) of shear wave speed (SWS) imaging and to validate the additional value of QM in the diagnosis of breast lesions. From September 2014 to February 2015, conventional ultrasound and SWS imaging were performed in 338 women with 361 breast lesions. Binary logistic regression was used to identify associated factors for QM. Sensitivity, specificity and the area under receiver operating characteristic (ROC) curve (AUC) among maximum SWS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Acoustic Radiation Force Imaging (ARFI) is an internal technique that superimposes tissue elasticity data over a conventional greyscale ultrasound image. Shear waves exciting the target tissue are generated within a fixed‐size (0.7 × 0.7 mm) region of interest (ROI) sampling box where data such as tissue displacement, speed of propagation of the shear waves, and tissue stiffness are obtained 11,12 . Displacement of tissue is higher in soft tissue (fat) and lower in stiff tissue (tendon).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic Radiation Force Imaging (ARFI) is an internal technique that superimposes tissue elasticity data over a conventional greyscale ultrasound image. Shear waves exciting the target tissue are generated within a fixed‐size (0.7 × 0.7 mm) region of interest (ROI) sampling box where data such as tissue displacement, speed of propagation of the shear waves, and tissue stiffness are obtained 11,12 . Displacement of tissue is higher in soft tissue (fat) and lower in stiff tissue (tendon).…”
Section: Introductionmentioning
confidence: 99%
“…A two-dimensional (2D) quality measurement map (QM) was used to assess the quality of shear wave propagation for data acquisition and data processing. 12 When ARFI is activated, the sampled tissue data is qualitatively and quantitatively evaluated using a proprietary algorithm, and shear wave velocity is measured in meters per second (m/s). High shear wave velocity and low shear wave displacement denotes a "stiff" structure such as bone, whereas low shear wave velocity and high shear wave displacement denotes a less stiff structure, such as muscle belly or adipose tissue.…”
mentioning
confidence: 99%
“…Several studies report that QSE with B-mode ultrasound improves the diagnosis and evaluation of breast lesions [10]. However, QSE has limitations as it is highly operator dependent and incapable of deeper organ imaging [11]. Moreover, the quantitative information provided by SWE gives better performance compared to QSE [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SWE has emerged as a new imaging tool that has high reproducibility, capable of deeper organ imaging and has low operator dependency compared to QSE [13]. It has shown potential performance in breast, liver, and prostate lesion detection and diagnosis [11], [12], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Large full-thickness tears and revision rotator cuff repairs are more problematic. 12 Thon et al 19 however, reported encouraging results for the use of bioinductive implants in 23 patients who underwent arthroscopic repairs of large-massive full-thickness rotator cuff tears, augmented with bioinductive collagen implants after capsular release. They found that 96% (22/23) of the repairs had healed by 2 years, with evidence of new tendon formation on ultrasound and magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%